The Effectiveness of Teams Games Tournament Using Google Sites with Local Wisdom in Teaching Flat Shapes to Elementary Students - Suardipa, I Putu; Sedana, I Made; Ardiyasa, I Nyoman Suka; Kurniawan, Made Ferry (Universitas Pendidikan Ganesha, 2024)
Mastery of flat shape concepts in elementary mathematics remains a challenge due to monotonous teaching methods and limited use of interactive media. This issue highlights the need for innovative learning models that integrate technology and local cultural values to enhance students' conceptual understanding. This study aims to analyze the differences in flat shape mastery between students using the Teams Games Tournament (TGT) model assisted by Google Sites with local wisdom content and those following conventional learning methods. The research employs a quasi-experimental method with a pre-test post-test control group design. The population consists of 86 fifth-grade elementary school students, with a randomly selected sample comprising 25 students in the experimental group and 27 students in the control group. Data were collected through flat shape concept comprehension tests and analyzed using validity and reliability tests, item discrimination, item difficulty levels, descriptive analysis, N-Gain score analysis, normality tests, homogeneity tests, and an independent N-Gain score t-test. The analysis results show that students in the experimental group using the TGT model assisted by Google Sites with local wisdom content experienced significantly higher mastery improvement compared to students in the control group. This finding demonstrates that interactive media based on local wisdom effectively enhances students' understanding of flat shape concepts.